A fractal-based approach for reconstructing pore structures of GGBFS-blended cement pastes. (30th December 2020) - Kim, Jiyoung; Choi, Seongcheol
Highlights: Microstructural characteristics of GGBFS-based cement pastes were evaluated. Fractal-based reconstruction procedure for cementitious materials was investigated. Fractality of pore regions were quantified using two fractal types. Pore structures were reconstructed by combining three BFU types per pore region. Changes in pore structures by hydration could be analyzed using reconstructed ones. Abstract: The durability and mechanical behavior of cementitious materials can be substantially affected by changes in pore structure that occur during the hydration process. An accurate analysis of pore structure thus plays an important role in the interpretation and prediction of the performance of cementitious materials. This study investigated an analytical fractal reconstruction procedure for cementitious materials and demonstrated its application by reconstructing pore structure using fractal theory from a geometric perspective. For this purpose, microstructural characteristics of ground granulated blast-furnace slag-based cement pastes were evaluated using the results of mercury intrusion porosimetry measurements. Fractal characteristics in the mesopores and larger capillary pores were quantified using the pore surface fractal type, whereas those in the middle capillary pores were quantified using the solid mass fractal type. As a result of reconstructing pore structure, variations in the cumulative pore volumes appeared similar to those of the measured pore structure. Moreover, the differential pore size distributions of all pore regions were quantified as the fractal dimensions. These results indicated that the investigated methodology can be practically applied for the analysis of changes in pore structure caused by hydration in cementitious materials.